HARMONISASI MULTI SISTEM UNTUK REVITALISASI PENDIDIKAN TINGGI DAN PENINGKATAN MUTU SDM LULUSAN PROGRAM STUDI - Surono (LPPM Universitas Asa Indonesia, 2016)
The aim of this study is to conduct identification of room for harmonization among the systems to promote high quality output in higher education. The method used are the survey on all available systems of National Education System, National Training, National Qualification Framewrok of Indonesia, National Competency Standards Systems, RMCS, and AQRF system. The enrichment were found out of the above sytems that need (1) to set up the policy of harmonization on NQF in ministries level, (2). To set up the similar meaning, interpretation, and practice on all terminologies of qualified human resource among the sectors, (3) the need for rapid assessment to fill the existing shortages of qualified, and certified professionals in all sectors. (4) to encourage the development of competency standards by Public Private Academia Partnership among all stakeholders, (5) to develop instructional design of vocational model that traceable with NQF and SKKNI, (6) to develop certification schemes based on occupation mapping, (7). Joint cooperation system using the valuable AQRF 2018.